Non-aqueous Conductimetric Titrations of Phenolic Compounds with Tetra-n-butyl Ammonium Hydroxide and Amines with Perchloric Acid in Acetonitrile Solvent - Ramasami, P.; Ramburrun, P. (Asian Journal of Chemistry, 2010)
Non-aqueous conductimetric titrations were carried out for phenolic acids (2-nitrophenol, 4-nitrophenol, 3-methoxyphenol and o-cresol) and their mixtures dissolved in acetonitrile with tetra-nbutyl ammonium hydroxide dissolved in propan-2-ol. Also nonaqueous conductimetric titrations were carried out for amines (aniline and benzylamine) and their mixtures dissolved in acetonitrile with perchloric acid dissolved in dioxane. The non-aqueous conductimetric titration results have been interpreted in terms of the relative acid and basic strength of the phenolic acids and the arnines. The results distinguish non-aqueous titrations from those carried out in aqueous medium